2022
DOI: 10.3390/cancers14092324
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Side Effects of Chemotherapy and/or Radiation Therapy for Head and Neck Cancer: A Literature Review

Abstract: Radiotherapy and chemotherapy represent important treatment modalities for head and neck cancer. Rhinosinusitis and smell alterations are common side effects in the sinonasal region. This review will summarize and analyze our current knowledge of the sinonasal side effects of chemotherapy and/or radiation therapy for head and neck cancer (HNC), with a specific focus on mucosal and olfactory disorders. A review of the English literature was performed using several databases (PubMed, Embase, Cochrane, Scopus). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…In addition, although statistically insignificant, the TL group contained a marginally greater proportion of patients who underwent radiation therapy or chemotherapy after surgery. The detrimental effects of chemotherapy and radiotherapy on nasal ciliary clearance and sinus function, along with alterations in the sinonasal mucosa ranging from congestion to atrophic changes, have been documented in numerous recent publications, as this may have possibly been one of the confounding factors in our study 37–40 . However, considering that the main reason for TL is mostly due to advanced laryngopharyngeal cancers, the effects of additional chemoradiation on the sinonasal mucosa and microstructures should be considered as the major limitation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, although statistically insignificant, the TL group contained a marginally greater proportion of patients who underwent radiation therapy or chemotherapy after surgery. The detrimental effects of chemotherapy and radiotherapy on nasal ciliary clearance and sinus function, along with alterations in the sinonasal mucosa ranging from congestion to atrophic changes, have been documented in numerous recent publications, as this may have possibly been one of the confounding factors in our study 37–40 . However, considering that the main reason for TL is mostly due to advanced laryngopharyngeal cancers, the effects of additional chemoradiation on the sinonasal mucosa and microstructures should be considered as the major limitation.…”
Section: Discussionmentioning
confidence: 92%
“…in numerous recent publications, as this may have possibly been one of the confounding factors in our study. [37][38][39][40] However, considering that the main reason for TL is mostly due to advanced laryngopharyngeal cancers, the effects of additional chemoradiation on the sinonasal mucosa and microstructures should be considered as the major limitation. To overcome this factor, a subgroup analysis regarding on the adjuvant chemo-or radiation status might be fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…Late toxicities (tissue changes occurring at least 90 days after RT end) are represented by osteoradionecrosis, xerostomia, fibrosis, thyroid dysregulation, sensorineural hearing loss, myelitis, and pharyngeal or laryngeal stenosis [32][33][34]. In the sinonasal district, due to the dysregulation of nasal mucociliary clearance (MCC), RT is responsible for a variety of disruptions and alterations [35].…”
Section: Nasal Cytology In Head and Neck Cancer Chemoradiotherapymentioning
confidence: 99%
“…Furthermore, Cooper et al demonstrated that late clinically relevant alterations rarely occurred with doses lower than 50 Gy, while oral and nasal ulcerations were extremely rare for doses < 65 Gy [36]. In a recent review, the percentage of patients affected by CRSr ranged from 7% to 86.1%, and the most common pathogens isolated in the CRSr group were Staphilococcus aureus, Streptococcus viridans, and Pseudomonas aeruginosa [35]. Moreover, Stoddard et al found that Staphilococcus aureus and Pseudomonas aeruginosa represented the most common bacteria in sinonasal cultures of patients affected by CRSr and concluded that the bacteriology of CRSr seemed to be similar to the usual microorganism colonization of non-radiated patients [28].…”
Section: Nasal Cytology In Head and Neck Cancer Chemoradiotherapymentioning
confidence: 99%
“…These side effects seemed to be related to radiation dose on the olfactory area and nasal cavities, but different degrees of recovery were observed. Therefore, it became important to establish the severity of chronic rhinosinusitis and olfactory dysfunction in order to find strategies to support patients and improve their quality of life [ 6 ].…”
mentioning
confidence: 99%